2020
DOI: 10.29252/archhygsci.9.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Heavy Metals, Namely Lead, Cadmium, and Chromium, in Hair Color Available in the Markets of Qom, Iran

Abstract: In recent years, cosmetic industry has experienced a significant progress, including the production of various types of cosmetics, such as soaps, creams, face powder, tanning lotions, toothpaste, and lipsticks, for the skin, hair, teeth, body, and nails care (1). Based on previous research, the consumption of cosmetic products is very common in Iran. According to the statistics, Iran and Saudi Arabia have the highest cosmetic consumption rate in the Middle East; in this regard, about $ 2.1 million is spent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Recent research has shown that there is no safe limit for Pb, due to its neurotoxic nature (17). Pb has an important role in increasing the blood pressure and risk of cardiovascular diseases in adults, decreasing cognitive ability, and the formation of renal tumors (18,19).…”
Section: Assessment Of Toxic Elements and Peroxide Value In Lipsticks...mentioning
confidence: 99%
“…Recent research has shown that there is no safe limit for Pb, due to its neurotoxic nature (17). Pb has an important role in increasing the blood pressure and risk of cardiovascular diseases in adults, decreasing cognitive ability, and the formation of renal tumors (18,19).…”
Section: Assessment Of Toxic Elements and Peroxide Value In Lipsticks...mentioning
confidence: 99%